2007
DOI: 10.1002/nau.20423
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind, sham‐controlled evaluation of the effect of functional continuous magnetic stimulation in patients with urgency incontinence

Abstract: Magnetic stimulation was effective on urgency incontinence in comparison to sham stimulation in this small patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(85 citation statements)
references
References 27 publications
1
81
0
3
Order By: Relevance
“…[120][121][122] Other studies have shown equivalent efficacy to oxybutynin. 123,124 The efficacy of interferential low-frequency therapy has also been demonstrated in an RCT.…”
Section: Grade Of Recommendation: C1 (Electrical Stimulation) Not Apmentioning
confidence: 99%
“…[120][121][122] Other studies have shown equivalent efficacy to oxybutynin. 123,124 The efficacy of interferential low-frequency therapy has also been demonstrated in an RCT.…”
Section: Grade Of Recommendation: C1 (Electrical Stimulation) Not Apmentioning
confidence: 99%
“…12 There have been few randomized controlled studies with a small number of patients to verify the efficacy of magnetic stimulation for the treatment of OAB. 9,13 In our previous preliminary study, the effectiveness of magnetic stimulation therapy was evaluated in a randomized, crossover trial comparing the active stimulation and the sham stimulation in a small group of patients (16 males and 23 females). 13 The number of leaks/week in the bladder diary, the total score of International Consultation on Incontinence-Questionnaire: Short Form and maximum cystometric capacity by urodynamic study were significantly improved as compared with the initial levels in the active stimulation group, but not in the sham stimulation group.…”
Section: Introductionmentioning
confidence: 99%
“…По результатам работы было зафикси-ровано улучшение всех параметров через 10 нед после начала и в конце исследования в группе активного лечения [30]. В 2014 г. группа ученых во главе с T. Yamanishi опубликовали данные мультицентрового рандомизированного слепого плацебоконтроли-руемого исследования, включившего 151 женщину с ИНМ.…”
Section: том 7 Volunclassified
“…отмечали сохранение терапевтического эф-фекта через 24 нед после окончания курса процедур у 9 из 17 пациентов, T. Suzuki и соавт. получили анало-гичные результаты у 6 из 16 больных через год после лечения, при этом не была использована какая-либо дополнительная терапия [30,32]. Однако F. G. Almeida и соавт., наблюдая немедленное клиническое улучше-ние у 34 пациентов из 91, констатировали рецидив симптоматики в 94 % случаев через год после прекра-щения лечения [33].…”
Section: том 7 Volunclassified